Gold as a hedge for inflation risk in Malaysia - Muhamad Senan, Mohamad Khair Afham (2013)
This study examines the long run and short run inflation hedging effectiveness of gold in Malaysia during the period of 1971 until 2011 by using monthly data. This study employed Engle-Granger cointegration test and Johansen cointegration test for long run analysis and Threshold Vector Autoregression (TVECM) for short run analysis. In the long run analysis, results from Engle Granger cointegration tests show that the cointegration between gold price and CPI is exist and gold is effective in hedging against inflation risk in Malaysia. These results are consistent with the Johansen cointegration test that has been employed. From Tsay’s linearity test, this study detected the nonlinearity of the relationship between gold return and inflation rate and thus, allowed to proceed with nonlinear TVECM analysis. In short run, gold is proven to be effective as a hedging tool against inflation but the effectiveness varies on different price momentum (based on threshold) and the time period. It is found that during the high momentum regimes, gold return is able to hedge against inflation in Malaysia better than during low momentum regime. This study also found that from 2000 until 2011, the ability of gold in hedging against inflation is much better than the whole period of study. As for studying the causality relationship between gold return and inflation rate, this study found that only inflation does granger cause gold return and gold return does not granger cause inflation rate. The implication of the results of this study are microeconomic entities can have better and wider option to diversify their assets, helps in decision making process for investors helps government to star giving better awareness to citizens.